AWOL - the ancient world online (Institute for the Study of the Ancient World, New York University, 2009)
This project began with a series of entries under the heading AWOL on the Ancient World Bloggers Group Blog. It was moved to its own space beginning in 2009. The primary focus of the blog will be notice and comment on open access material relating to the ancient world, but it also includes other kinds of networked information as it becomes available. The ancient world here is conceived as it is at the Institute for the Study of the Ancient World at New York University. That is, from the Pillars of Hercules to the Pacific, from the beginnings of human habitation to the late antique / early Islamic period
Keywords: Website; Weblog